The Influence of Self-Efficacy and Social Support on Work Readiness of Business Digital Students at SMKS NU Gresik (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Entering the workforce requires thorough preparation given the increasingly tight competition and challenges. One of the ongoing issues is the imbalance between the number of job seekers and the available job opportunities, which also contributes to high unemployment rates, especially among graduates of Vocational Secondary Schools (SMK). Based on tracer study results from the Business Digital Program at SMKS NU Gresik, there are still some graduates who have not secured employment after graduation. This is despite the fact that SMKs are designed to produce job-ready graduates through the provision of technical and vocational skills. This research employed a quantitative method, with primary data collected directly from respondents via online questionnaires distributed using Google Form links. The collected data were then analyzed using multiple linear regression techniques with the help of IBM SPSS version 25 software. The results showed that self-efficacy has a positive influence on the work readiness of students in the Business Digital program at SMKS NU Gresik. Additionally, social support also influences their work readiness. Simultaneously, both self-efficacy and social support have a significant combined effect on the students’ readiness to enter the workforce.
Keywords: Self-Efficacy, Social Support, Job Readiness